Economics of public utility - Choudhury, Rabindra Kumar (Bombay, 1986)
Public Finance and Fiscal Policy is a comprehensive text book which not only deals with syllabi content of Gauhati and other Universities of north-eastern and eastern regions, but is also provided with a broader base to benefit the students of other Indian Universities. The syllabi of Delhi University and of some other Central Indian and South Indian Universities have been consulted before structuring textual contents of the book.
Keywords: Economics